Ni2+-Doped Garnet Solid-Solution Phosphor-Converted Broadband Shortwave Infrared Light-Emitting Diodes toward Spectroscopy Application - Yuan, Lifang; Jin, Yahong; Wu, Haoyi; Deng, Kaiyuan; Qu, Bingyan; Chen, Li; Hu, Yihua; Liu, Ru-Shi (ACS applied materials & interfaces, 2022)
Broadband shortwave infrared (SWIR) light-emitting diodes (LEDs), capable of advancing the next-generation solid-state smart invisible lighting technology, have sparked tremendous interest and will launch ground-breaking spectroscopy and instrumental applications. Nevertheless, the device performance is still suppressed by the low quantum efficiency and limited emission bandwidth of the critical phosphor layer. Herein, we report a high-performance Ni2+-doped garnet solid-solution broadband SWIR emitter centered at ∼1450 nm with a large full-width at half-maximum of ∼300 nm, thereby fabricating, for the first time, a directly excited Ni2+-doped garnet solid-solution phosphor-converted broadband SWIR LED device. A synergetic enhancement strategy, adding a fluxing agent and a charge compensator simultaneously, is proposed to deliver a more than 20-fold increase of the SWIR emission intensity and nearly 2-fold improvement of the thermal quenching behavior. The site occupation and mechanism behind the synergetic enhancement strategy are elucidated by a combination of experimental study and theoretical calculation. A prototype of the SWIR LED with a radiation flux of 1.25 mW is fabricated and utilized as an invisible SWIR light source to demonstrate the SWIR spectroscopy applications. This work not only opens a window to explore novel broadband SWIR phosphors but also provides a synergetic strategy to remarkably improve the performance of artificial SWIR LED light sources.